Hybrid technique and total arch replacement combined with frozen elephant trunk in acute aortic dissection involving the aortic arch: a multi-center propensity-matched cohort study - Hang Zhang; Ruoyu Zhang; Min Yu; Zhongxiang Yuan; Dewei Qian; Wen Chen; Fuhua Huang; Xin Chen; Xiaodi Wang (BMC Cardiovascular Disorders)
Abstract Background The aim of this study was to investigate whether the hybrid technique yields superior outcomes in comparison with the total arch replacement combined with frozen elephant trunk (TAR + FET) for acute aortic dissection (AAD) involving the aortic arch. Methods This retrospective cohort study using propensity-score matching included patients with AAD involving the aortic arch admitted to Nanjing First Hospital and Shanghai General Hospital from January 2015 to June 2020. The in-hospital and mid-term outcomes were compared between patients who received hybrid treatment (n = 136) and those who received TAR + FET (n = 415). Study end points included in-hospital mortality and morbidity, and mid-term rates of death from all causes, stroke, and aortic re-intervention. Results A total of 121 pairs were formed after matching. In-hospital mortality did not differ between hybrid versus TAR + FET groups (5.8% vs. 7.9%, P = .860). Up to 6 years, patients treated with TAR + FET were associated with reduced rate of aortic re-intervention (HR 0.21, 95% CI 0.05–0.97; P = .023). There was no difference in death from all causes and stroke. Conclusions Hybrid technique and TAR + FET showed comparable mid-term survival. Hybrid technique showed higher rate of aortic re-intervention and should therefore be applied with great caution in patients with AAD involving the aortic arch.